Genetic diversity of Gracilaria changii (Gracilariaceae, Rhodophyta) from west coast, Peninsular Malaysia based on mitochondrial cox1 gene analysis - Yow, Yoon Yen *; Lim, Phaik Eem; Phang, Siew Nooi * (Springer, 2011)
Mitochondrial cytochrome c oxidase subunit I (cox1) was employed to investigate the intraspecific genetic diversity of Gracilaria changii collected from various localities distributed along the west coast of Peninsular Malaysia. Gracilaria changii is an agarophyte with potential for commercialization in Malaysia as it has high yields of good quality agar with high gel strength for the production of food grade agar and agarose. The phylogeographic aspect of G. changii has not been studied despite its abundance and potential commercialization. In this study, six mitochondrial haplotypes (C1–C6) were revealed from 62 specimens varying by 0–3 bp over 923 bp. Results indicate that haplotype C1 is the common ancestor and the most widespread haplotype due to its prevalence in Morib, Gua Tanah, Middle Banks, Batu Besar, Batu Tengah, Sungai Pulai, and Kuala Sungai Merbok. In this study, Morib was suggested as contributing the highest intrapopulation diversity with the identification of three haplotypes. The mitochondrial marker cox1 is a highly divergent mitochondrial marker and is applicable for studies on species identification and assessment of genetic diversity of G. changii.